Relationship of 7P Marketing Mix and Consumers' Loyalty in Traditional Markets - Hariyani Dwi Anjani; Irham Irham; Lestari Rahayu Waluyati (Agro Ekonomi, 2018)
The existence of the traditional market as a center of most people’s economic activities in Indonesian society has begun to be displaced by the modern market. Improvement in service quality is important in increasing consumers’ loyalty in order to retain them.  The purposes of this research are: 1) to know the level of marketing mix of (Product, Price, Place, Promotion, People, Process, in 7P traditional market; 2) to know the level of traditional market consumer’s loyalty of and 3) to determine the relationship between marketing mix implementation with consumer’s loyalty. There were 180 traditional market consumers selected by incidental sampling method from 8 traditional markets in 6 districts among 5 provinces all over Indonesia. Checklists and Likert scale questionnaires were used as tools in this study. Descriptive method was used to analyze data. Based on analysis results, it is known that, according to the consumers, the level of marketing mix implementation in traditional markets is high with an average value of 74.07%. The marketing mix elements in order to arrange from the highest to the lowest level of implementation are respectively those termed People, Process, Physical Evidence, Price, Place, Product, and Promotion. The People element is the highest in level. This shows that traders’ friendliness, alacrity, and honesty are still the hallmarks of traditional markets. The Promotion element is the lowest in level because most of the merchants do not implement proper promotion. The average of consumers’ loyalty level in traditional markets is 77.61%, which is considered high in the category. The 7P’s marketing mix, except for the Product aspect, have a positive and significant correlation with consumer loyalty, but it is still relatively weak. The consumers would continue to repurchase in the traditional markets and recommend that others also shop there.